Constitutional corruption in India: an analysis of two Bharatiya Janata Party scandals - Krishna K. Tummala (Public Administration and Policy, 2020)
Purpose – This paper focuses on two examples of constitutional corruption in India where the constitution is used for questionable political reasons by the Bharatiya Janata Party under the leadership of Prime Minister Narendra Modi. Design/methodology/approach – The paper relies on public documents and media reports to analyse Prime Minister Modi's handling of the purchase of Rafale jet fighters from France and the revocation of Articles 370 and 35A which resulted in the division of the State of Jammu and Kashmir. Findings – Constitutional and democratic norms were violated in both cases, but the Supreme Court did not find any irregularities in the sale of the Rafale jet fighters. The second case is under challenge in the Supreme Court. The analysis reveals how the Modi government has undermined democratic values and used constitutional provisions to pursue its partisan and ideological agenda. Originality/value – The paper focuses attention on the often neglected topic of constitutional corruption in India.